Seed Breaking Dormancy Technique and Growth of Screw Tree (Helicteres isora Linn.) Seedlings - Nazhira Firda Yulia; . Supriyanto; Diana Prameswari (Jurnal Perbenihan Tanaman Hutan, 2021)
Screw tree is a shrub from family Malvaceae that has many benefits in pharmacy. Screw tree seed has very hard seed coat, so the seed must be treated before germination. The aim of this research was to assess the characteristic of fruit and seeds, effect of seed breaking dormancy, and effect of NPK fertilizer dosage on the growth of screw tree (Helicteres isora) seedlings. The results indicated that screw tree fruits belong to dry fruits with capsule form and has 5 follicles that has different direction. Screw tree seed is orthodox type that has 9 ̶ 36 seeds in one follicle with triangle and square shape. Germination technique in laboratory with soaking the seeds in hot water 100oC until the water cool for 48 hours treatment produced the best germination amounting to 65.0%.  Germination technique in green house with soaking the seeds in hot water 100oC until the water cool for 24 hours treatment was the best germination amounting to 77.0%. Seedlings fertilized with 1 g NPK doses increased screw tree growth in diameter parameter of 6.35 mm and shoot-root ratio parameter of 3.9 compared to control.